Locally acting ACE‐083 increases muscle volume in healthy volunteers - Chad Glasser; Michael Gartner; Dawn Wilson; Barry Miller; Matthew L. Sherman; Kenneth M. Attie (2018)
ABSTRACT Introduction : ACE‐083 is a locally acting follistatin‐based therapeutic that binds myostatin and other muscle regulators and has been shown to increase muscle mass and force in neuromuscular disease mouse models. This first‐in‐human study examined these effects. Methods : In this phase 1, randomized, double‐blind, placebo‐controlled, dose‐ranging study in healthy postmenopausal women, ACE‐083 (50–200 mg) or placebo was administered unilaterally into rectus femoris (RF) or tibialis anterior (TA) muscles as 1 or 2 doses 3 weeks apart. Results : Fifty‐eight postmenopausal women were enrolled, 42 ACE‐083 and 16 placebo. No serious adverse events (AE), dose‐limiting toxicities, or discontinuations resulting from AEs occurred. Maximum (mean ± SD) increases in RF and TA muscle volume were 14.5% ± 4.5% and 8.9% ± 4.7%, respectively. No significant changes in mean muscle strength were observed. Discussion : ACE‐083 was well tolerated and resulted in significant targeted muscle growth. ACE‐083 may have the potential to increase muscle mass in a wide range of neuromuscular disorders. Muscle Nerve 57 : 921–926, 2018